Nursing work environment, professional self‐actualization and marketing of the nursing profession: Cross‐sectional study - Yelena Hazanov; Yulia Gehman; Rachel Wilf Miron; Ilya Kagan (Wiley, 2021)
Abstract Aim To explore associations between nurses' sense of professional self‐actualization, nursing work environment and their involvement in promotion and marketing of the nursing profession. Design A descriptive cross‐sectional study. Methods 144 nurses from various clinical fields completed a promotion and marketing activity questionnaire, selected items from the Brief Index of Self‐Actualization and a part of the Revised Nursing Work Index. Results Nurses' perception of their work environment and holding a master's degree in nursing were associated with their involvement in promotion activities [R2 = 0.27, F(4, 113) = 10.4, p < .001]. Nurses' perception of their work environment was associated with their sense of professional self‐actualization [R2 = 0.21, F(2, 121) = 16.5, p < .001]. Nurses' sense of professional self‐actualization did not contribute to the explanation of variance in their involvement in promotion of the nursing profession.